Kidney Evaluation in Hyperuricemia Rats Treated with Green Tea Leaves (Camellia sinensis L.) Extract - Putranty Widha Nugraheni; Chanif Mahdi (Sunan Kalijaga State Islamic University & Society for Indonesian Biodiversity, 2022)
Uric acid is an oxidation product of the xanthine oxidase enzyme found in extracellular fluid, and when it exceeds, uric acid will build up and cause hyperuricemia. TNF-α is released by epithelial cells and mesangial cells when inflammation occurs and causes apoptosis in epithelial cells, causing damage to kidney structures and initiating acute kidney poisoning. Green tea extract (Camellia sinensis L.) contains many antioxidants, especially flavonoids with potent antioxidant properties such as lipid peroxidase and free radical absorbers, inhibiting xanthine oxidase. This study expresses the potential of green tea extract on kidney repair caused by HUA. Twenty-four male albino rats (175-225 g) of Wistar strain being fed a high purine diet in 60 consecutive days and divided into six groups randomly, I: negative control, II: positive control, III: allopurinol, IV: green tea extract 150mg of body weight, V: green tea extract 300mg of body weight, and VI: green tea extract 600mg of body weight. Treatment was done for 14 days and measured by total creatinine levels, malondialdehyde levels, and kidney histopathology. The statistical analysis using One Way ANOVA and Post Hoc Tukey analysis by SPSS 23.0 proved that green tea extract with a dose of 600 mg/kg of body weight green could lower levels malondialdehyde of the kidney as much as 58.85% (p<0.01), decreased creatinine level by 24.5% (p>0.05), and improved kidney histopathology. This study proved that green tea extract is a promising alternative for hyperuricemia while improving kidney tissues and lowering malondialdehyde and creatinine levels.